2007
DOI: 10.1097/01.prs.0000254544.65054.95
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Microsurgery in Vietnam by a Charitable Organization: A 15-Year Experience

Abstract: Charitable organizations can help surgeons in developing countries master complex microsurgical techniques through short-term medical missions, donation of equipment and supplies, and the encouragement of institutional support. A continuing education program, including local conferences, microsurgical laboratory training facilities, and study abroad, can aid this introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…27,28 However, the missionbased service model has been criticized for being a temporary solution to a longitudinal problem. [7][8][9][10]16 In light of the criticism, it has been suggested that surgical mission and service trips be used as a bridge for the development of more long-term capacity to care for soft-tissue injuries. 24,25 Thus, given the flap success rate and dissemination of information demonstrated by LMIC-based orthopedic surgeons who participated in the SMART course, this study adds to the literature by providing a potential sustainable alternative to manage soft-tissue wounds and reduce amputation burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 However, the missionbased service model has been criticized for being a temporary solution to a longitudinal problem. [7][8][9][10]16 In light of the criticism, it has been suggested that surgical mission and service trips be used as a bridge for the development of more long-term capacity to care for soft-tissue injuries. 24,25 Thus, given the flap success rate and dissemination of information demonstrated by LMIC-based orthopedic surgeons who participated in the SMART course, this study adds to the literature by providing a potential sustainable alternative to manage soft-tissue wounds and reduce amputation burden.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] From a technical skill and equipment perspective, soft-tissue coverage procedures can be performed effectively in lowresource settings. 15,16 A substantial deficit in the number of surgeons trained to manage soft tissue defects and prevent amputation has been documented in LMICs. 4,17,18 Opportunities to improve soft-tissue wound care and reduce disability-adjusted life years by providing increased flap reconstruction training or access to plastic surgery services have been suggested in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Vietnam a 15 year continuing education program for microsurgery has helped local surgeons to master complex microsurgical techniques. Vietnam now has a cadre of surgeons very capable of performing these multifaceted surgical procedures (Merrell et al 2007). Also, in 2008, the continuing Physician Training Program brought 91 physicians, nurses, dentists and speech pathologists from 29 countries to Norfolk, Virginia, for 2 weeks of training.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Virtually every specialty has benefited from this technique. [1] It circumvents the limitations of pedicle flaps where the arc of rotation may be restrained, as well as local flaps where local tissues may be have been compromised by previous surgery or irradiation. Free tissue transfer allows the provision of customized, well-vascularized, healthy tissues from distant sites.…”
Section: Introductionmentioning
confidence: 99%